Pengembangan Modul Pembelajaran Matematika Berbasis Problem Posing untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa - Hulu, Mitra Verolina; Mendrofa, Ratna Natalia; Mendrofa, Netti Kariani; Telaumbanua, Yakin Niat (Pusat Studi Bahasa dan Publikasi Ilmiah, 2025)
This study was motivated by observations at UPTD SMP Negeri 1 Gunungsitoli Selatan, which indicated that students’ creative thinking skills were very low and the available teaching materials were limited. Students often struggled to understand the material and relied heavily on the teacher, highlighting the need for more effective learning resources. The purpose of this research was to develop a Problem Posing-based learning module that is valid, practical, and effective in enhancing students’ creative thinking skills. This study employed a development research design using the ADDIE model, comprising analysis, design, development, implementation, and evaluation stages. Data were collected using learning outcomes tests, validation questionnaires, and student response questionnaires, encompassing both quantitative and qualitative data. Quantitative data included validator scores, student responses, teacher feedback, and learning outcomes, while qualitative data comprised comments and suggestions from validators. The results showed that the developed module met validity criteria for content, language, and design. It was highly practical, with student practicality at 91.18% and teacher practicality at 96.42%. Furthermore, the module effectively improved students’ creative thinking, achieving an average score of 81.56%, categorized as very creative. In conclusion, the Problem Posing-based learning module successfully fulfilled the research objectives, providing a reliable, practical, and effective tool to support the development of students’ creative thinking skills in mathematics.